The Analisis Ketidaklengkapan Dokumen Rekam Medis Pada Kasus Rawat Inap Di Rsud Patut Patuh Patju Gerung - maliki, ahmad; Saimi, Saimi (Jurnal Kesehatan Qamarul Huda, 2018)
The purpose of this study is to investigate the uncomplete medical records documents in Patut Patuh Patju Hospital in 2017. The sample has 86 files and presented in the check list form. The result of the study shows the existence of the uncomplete documents in the data identities 84,83% complete and 15,17% uncomplete. The mean of the uncomplete clinical record is 22% while the complete record is 55,36%. Meanwhile, the uncomplete records of support file form is 8,5% and 32,13% is complete. This study concludes that the hospital needs to improve its medical records staff competence to produce decent documents. Keywords: Uncomplete, clinical record, identities record, support file